Referential gaps between Arabic and English - Alhendi, Noor; Baniamer, Asem (Frontiers in Education, 2024)
IntroductionThe study addresses the phenomenon of referential gaps between Arabic and English, highlighting the distinct referential behaviors each language employs during communication. These differences pose challenges to both language recipients and educators, creating obstacles for Arabic and English teachers and learners alike. Understanding these gaps is crucial for improving language learning and teaching processes.MethodsThe study investigates referential gaps by analyzing their manifestations across four linguistic levels: phonetic, lexical, morphological, and syntactic systems in both Arabic and English.ResultsThe findings demonstrate that the distinct referential behaviors in Arabic and English differ significantly across the analyzed linguistic levels. These differences contribute to the challenges faced by language learners and educators.DiscussionThe study underscores the importance of understanding referential gaps to address the challenges they present. By highlighting these differences, it provides insights into improving teaching strategies and fostering better communication between Arabic and English speakers.